Pembuatan Animasi Motion Graphic dalam Pembelajaran Akuntansi Bagan Akun Standar untuk Jurusan Akuntansi Politeknik Negeri Sriwijaya - Alisa Rosalina; Isnainy Azro; Alan Novi Tompunu (Teknik Komputer Politeknik Negeri Sriwijaya, 2021)
In the midst of this COVID-19 pandemic season, learning activities are carried out online and a lecturer is required to be more creative in terms of delivering material and information to students. One solution is learning animation videos. Therefore, the purpose of the research on